Dichotomy of decorin activity on the insulin‐like growth factor‐I system. (15th February 2013) - Morrione, Andrea; Neill, Thomas; Iozzo, Renato V.
<x xml:space="preserve">Abstract</x> The stromal‐specific proteoglycan decorin has emerged in recent years as a critical regulator of tumor initiation and progression. Decorin regulates the biology of various types of cancer by modulating the activity of several receptor tyrosine kinases coordinating growth, survival, migration, and angiogenesis. Decorin binds to surface receptors for epidermal growth factor and hepatocyte growth factor with high affinity, and negatively regulates their activity and signaling via robust internalization and eventual degradation. The insulin‐like growth factor (IGF)‐I system plays a critical role in the regulation of cell growth both in vivo and in vitro. The IGF‐I receptor (IGF‐IR) is also essential for cellular transformation, owing to its ability to enhance cell proliferation and protect cancer cells from apoptosis. Recent data have pointed to a role of decorin in regulating the IGF‐I system in both nontransformed and transformed cells. Significantly, there is a surprising dichotomy in the mechanism of decorin action on IGF‐IR signaling, which differs considerably between physiological and pathological cellular models. In this review, we summarize the current knowledge on decorin regulation of the IGF‐I system in normal and transformed cells, and discuss possible decorin‐based therapeutic approaches to target IGF‐IR‐driven tumors.